Comparative Studies on the Germination, Growth and Seedling Biomass of Two Promising Exotics in Rajasthan Desert (Prosopis juliflora (Swartz) Dc. And Acacia tortilis (Forsk.) Hayne ssp. tortilis) - Gupta, R. K.; Balara, G. S. (Indian Forester, 1972)
no abstract